2021
DOI: 10.33225/jbse/21.20.316
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Chemistry Curriculum Perspective: Teachers’ Perception of Lower-Secondary School Textbooks

Abstract: The (written) state curriculum is one of the cornerstones influencing education. Its specifically mediated by textbooks. In an open textbook market, the influence of the state curriculum is limited, and the main responsibility passes to individual schools or teachers. In order to understand education from the potential attainment of curriculum goals’ point of view, it is necessary to pay attention to the teachers’ textbook preferences. This research was focused on the field of lower-secondary chemistry educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 38 publications
4
35
0
3
Order By: Relevance
“…Sikorová (2010 found that 26% of teachers followed textbooks systematically, with only 55% changing the way topics were presented in their own lesson preparations. Vojíř and Rusek (2021) proved that this approach is not influenced by the length of teachers' practice. Li (2013) as well as Orafi and Borg (2009) offered an explanation by arguing it is a combination of teachers' lack of confidence, experience or subject knowledge which makes them rely on textbooks this much.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 90%
See 3 more Smart Citations
“…Sikorová (2010 found that 26% of teachers followed textbooks systematically, with only 55% changing the way topics were presented in their own lesson preparations. Vojíř and Rusek (2021) proved that this approach is not influenced by the length of teachers' practice. Li (2013) as well as Orafi and Borg (2009) offered an explanation by arguing it is a combination of teachers' lack of confidence, experience or subject knowledge which makes them rely on textbooks this much.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 90%
“…When preparing for their lessons, they consult textbooks as the primary source of information (Johansson, 2006;Sikorová, 2005). Whereas Sikorová (2010) reported over 30% of teachers using more than one textbook, Vojíř and Rusek (2021) found over 80% use even more textbooks. This could be explained by the teachers considering textbooks a convenient source of the materials they seek, nevertheless, Bakken (2019) found that some consider textbooks obligatory.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Textbooks play an irreplaceable role in promoting students' mastery of scientific knowledge and organization of learning activities. Besides, textbooks are the factor affecting students' academic performance (Aldahmash et al, 2016;Andersen, 2020;Polikoff, 2015), and the guarantee for teachers to implement curriculum standards (Hill, 2001), so it is necessary to examine the textbooks (Vojíř & Rusek, 2021). Under the standards-based reform, standards become the important basis of measurement, guide the curriculum development and classroom teaching, and put forward clear goals and expectations for teachers to improve teaching quality and students to improve their academic performance (Troia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%